Potential of Biduk Layar Traditional Sports Tourism as a Tourist Attraction in the City of Palembang - Widya Handayani; Lestari, Hikmah; Junaidi, Ilham Arvan (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2024)
The development of sports is currently growing from time to time, many people enjoy sports activities. The development of sports is currently also being used by several sectors to develop, including the tourism sector. The aim of this research activity is to attract local tourist attractions by involving traditional sports in an area that has different characteristics and customs. This research is a qualitative study to look at the potential for traditional sports tourism in the Big Dipper Sailing (BIDAR) in the city of Palembang. The results of this research are that Bidar traditional sports have high potential for the tourist attraction of the city of Palembang.